Suicide prevention in the virtual environment: strategies for dissemination and metrics for a website (Research, Society and Development, 2021)
Suicide is a multifactorial behavior and is a public health problem. The virtual environment is a relevant strategie to prevent suicide. Aim: The aim of the project was to analyze associations between strategies for dissemination and daily accesses to a website for prevention of suicidal behavior. Methods: A Quantitative study was developed from 2019 to 2020 with the InspirAção’s website. The data collection was made through Google Analytics, social media platforms (Facebook and Instagram), newspapers and lectures records. The data was analyzed using descriptive statistics, Mann-Whitney test and Spearman correlation. Results: The strategies of dissemination were associated with a greater number of access, new users, page views and a lower rejection rate. Conclusions: Low-cost dissemination strategies are promising to promote access to resources for suicide prevention and to disseminate scientific knowledge in an understandable and accessible way.